Outcome Transcatether Patent Ductus Arteriosus Closure in Children (Medico Legal Update, 2021)
Objective: To evaluated outcome transcatether PDA closure and differentiated LVEDD, EF pre and posttranscatether PDA closure. Methods: Hospital registry was reviewed and data about patients characteristics,PDA size, device occluder and outcomes were retrieved. An descriptive analytic study with a retrospectivedesign was conducted on all medical records of PDA pediatric patients who received definitive transcatheterPDA closure at IDIK and were treated at the Department of Child Health, Dr. Soetomo Hosptal from January2017 until December 2019. The variables studied are: outcome transcatether PDA closure (complete closure,residual shunt, emboli device, obstruction pulmonaly artery, obstruction Aorta descendent, hemolysis,LVEDD and EF). Post catheterization included a follow up of immediately, 1 day, 1 month, 3 months, 6months, and 12 months after catheterization. The data were processed and statistical comparative tests werecarried out. Results: There were 101 subjects, of whom were 33 males, who underwent transcatether closureof PDA during study periode. The diameter PDA ranged from 1-7.5 mm, with median 3.4 mm. Medianage 4.3 years (4 months-18 years), median body weight was 15.4 (5 – 45) kg. Device could be deployed inall patients, in which ADO I 65%, ADO II 15%, Nit Occlude 2% and MFO 19%. Immediately Completeclosure was achieved in most patiens (92,1%) and small residual shunt (7,9%), no major complicationduring or after procedure. Most patient were discharged from hospital at 3 day after procedure. LVEDD andEF was decreased after intervention transcatether closure (P